Effectiveness of Binahong Leaf Decoke (Anredera Cordifolia) on the Healing of Perineal Wounds in Post-Post Mothers - Novi Yulianti (Yayasan Media Utama Sains, 2025)
Perineal wounds are a common condition experienced by postpartum mothers following vaginal delivery and may lead to complications if not properly managed. Optimal wound care is essential to accelerate healing and prevent infection. One potential complementary therapy is boiled binahong leaves (Anredera cordifolia), which are known to have anti-inflammatory, antibacterial, and tissue regeneration properties. This study aimed to determine the effectiveness of binahong leaf decoction on perineal wound healing in postpartum mothers. This study employed a quasi-experimental design with a one-group pretest-posttest approach involving 52 postpartum mothers in the Sagulung District, Batam City, from October to December 2024. Samples were selected using purposive sampling. The REEDA scale was used to assess wound healing, and data were analyzed using a paired t-test. The results showed that the mean perineal wound score decreased from 9.2 ± 2.1 before the intervention to 3.8 ± 1.5 after the intervention. Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant difference before and after the intervention. In conclusion, boiled binahong leaf decoction is effective in accelerating perineal wound healing in postpartum mothers. This therapy has the potential to be an accessible, cost-effective, and practical complementary treatment in midwifery practice.